Targeting oxidative stress and metal imbalance in cerebral ischemia: the neuroprotective role of sodium valproate - Mustafa Ulaş; Ömer Gökay Argadal; Ebru Bardaş Özkan (Scientific Reports)
Abstract In brain ischaemia (BI), the oxidative and ionic stresses lead slowly but definitely to the injury of neurones. The present investigation is looking to check the status of certain oxidative stress markers and trace elements which are induced in response to brain ischaemia with sodium valproate (VPA), a neuroprotective agent, in the rats exposed to the model of BI. Although VPA is already used for clinical purposes, it deserves careful examination of the potentially detrimental effects of VPA in conditions of ischaemia closely linked to hepatotoxicity and thrombocytopenia. Forty rats were randomly assigned into five groups (n = 8 per group): Control, Sham, Brain Ischaemia (BI), BI + Valproic Acid (VPA), and VPA only. Ischaemia was induced in the BI and BI + VPA groups by bilateral occlusion of the common carotid arteries for 30 min. VPA was administered orally at a dose of 100 mg/kg daily for seven days in the BI + VPA and VPA-only groups. This dose was based on previous preclinical safety and efficacy data. Control, Sham, and BI groups received saline. The Sham group underwent surgical procedures without carotid occlusion. The biochemical investigations pertaining to cortical tissue demonstrated the fact that BI has decreased all antioxidant enzyme levels of SOD, CAT, GPx, and those of trace elements such as Mg, Zn, and Se. At the same time, malondialdehyde (MDA) and neurotoxic metals (Cr, Fe, Cu) increased. These changes brought by BI were restored through treatment with VPA on oxidative stress and the restoration of trace element balance along with reductions in those associated with oxidative damage. The results thus reinforce the capacity of VPA for neuroprotective benefits against ischaemic damage inflicted within brain tissue and hence merit the further exploration of the mechanistic action of this therapeutic A.